2017
DOI: 10.4103/0253-7176.207338
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenology and Treatment Response in Catatonia: A Hospital Based Descriptive Study

Abstract: Background:Literatures regarding clinical symptomatology and treatment response of catatonia are very few.Objective:To assess onset, clinical profile, diagnostic break up, treatment response and outcome in patients diagnosed as Catatonia, reported to a tertiary care hospital.Methods:The present study was a cross-sectional descriptive study conducted in indoor of Mental Health Institute (Centre of Excellence), S.C.B. Medical College, between March 2015 to March 2016. A total of 34 patients were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 28 publications
4
13
0
Order By: Relevance
“…The study showed catatonia to be occurring commonly in young, having its onset in twenties (24.63 years) which is in accordance with previous studies. 7,[10][11][12] It was found to be common in males, patients with high school education, Hindu religion, housewives and semiskilled workers, patients from mostly rural background, which again matches with other studies from India and represented profile of the majority of the patients. [10][11][12] Few patients had a family history of psychiatric illness (20%) suggestive of possible genetic etiology that is comparable with other studies.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…The study showed catatonia to be occurring commonly in young, having its onset in twenties (24.63 years) which is in accordance with previous studies. 7,[10][11][12] It was found to be common in males, patients with high school education, Hindu religion, housewives and semiskilled workers, patients from mostly rural background, which again matches with other studies from India and represented profile of the majority of the patients. [10][11][12] Few patients had a family history of psychiatric illness (20%) suggestive of possible genetic etiology that is comparable with other studies.…”
Section: Discussionsupporting
confidence: 72%
“…7,[10][11][12] It was found to be common in males, patients with high school education, Hindu religion, housewives and semiskilled workers, patients from mostly rural background, which again matches with other studies from India and represented profile of the majority of the patients. [10][11][12] Few patients had a family history of psychiatric illness (20%) suggestive of possible genetic etiology that is comparable with other studies. [11][12] Substance use disorder was found to be less common in our patients, compared to the sample from other studies 7 which might be due to small sample size.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations